Assessing the Social and Economics Aspect of Integrative Medicine in Malaysia - Catherine, Lim Mei Jing (Universiti Malaysia Sarawak, (UNIMAS), 2022)
This present study is conducted to examine the social and economic impact of integrative medicine in Malaysia. A total of 485 respondents were recruited in this study. Convenience sampling and snowball sampling approaches are being employed in this research. Self-administrative questionnaires are distributed through online (SoGo platform) and offline approaches. The offline approach, we distribute questionnaires in few places such as Kuching Waterfront, Chung Chinese physicians and acupuncture center, Tribal Kuching and Friendship Park Kuching. Before participating the online survey, consent form is given to participants. In the questionnaires, it include demographic background, general health profile, disease profile, usage and satisfaction towards traditional and complementary medicine (T&CM) and willingness to pay of T&CM. The result of the study found that there is significant difference in individual spending on T&CM across household income. Besides, our results showed to recover to perfect health, the respondents are willing to pay on average RM41,437.09 on T&CM for an additional QALY. Finally, Last but not least, our result presented those apply for complementary approach, with chronic disease are reported lower WTP/QALY values